Dental management of a patient with down syndrome: a case report and review of literature - Khandelwal, Deepak; Kalra, Namita; Tyagi, Rishi; Khatri, Amit; Kumar, Sunil; MM, Afsal (Indian Journal of Case Reports, 2019)
Down syndrome (DS) is the most common chromosomal abnormality which affects numerous organs, including the orofacial region. Patients with DS may not be cooperative during dental treatment, and in cases of complex treatment, it is necessary to use oral or inhaled sedation and/or general anesthesia, which represents safe and efficient treatment resources. This article reports a management of DS in a 7-year-old male patient who came to the Hospital of New Delhi with the chief complaint of pain in lower right back tooth region. Due to the uncooperative nature of the patient, dental treatment was done under general anesthesia in which multiple dental restoration and extraction were done.